2015
DOI: 10.1002/dvdy.24262
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of craniofacial developmental trajectories among avian embryos

Abstract: Background Morphological divergence among related species involves changes to developmental processes. When such variation arises in development has garnered considerable theoretical interest relating to the broader issue of how development may constrain evolutionary change. The hourglass model holds that while early developmental events may be highly evolvable, there is a phylotypic stage when key developmental events are conserved. Thus, evolutionary divergence among related species should tend to arise afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…This method allows pooling of embryos that are approximately the same age (e.g., within 1 day for E11.5 mouse embryos). Previous results have shown that the combination of age and size generates a more linear regression than either variable alone, possibly due to the occasional difficulty of counting tail somites (Smith et al, ). Once age and size have been corrected for, the shape differences between the two lines represent the majority of the remaining variation (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…This method allows pooling of embryos that are approximately the same age (e.g., within 1 day for E11.5 mouse embryos). Previous results have shown that the combination of age and size generates a more linear regression than either variable alone, possibly due to the occasional difficulty of counting tail somites (Smith et al, ). Once age and size have been corrected for, the shape differences between the two lines represent the majority of the remaining variation (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…; Adams and Collyer ; Collyer and Adams ; Smith et al. ). Trajectories can diverge from each other at different points in space and time.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, quantification of both ontogenetic and static allometry is a critical component of the phenotypic analysis of any mutant. A useful tool in such analyses is to do a combined analysis of shape and size, or form space, by adding centroid size back into a morphometric analysis (Mitteroecker and Bookstein 2008; Smith et al 2015). …”
Section: Quantifying Variationmentioning
confidence: 99%
“…Recent studies have used morphometrics and 3D imaging to quantify variation in craniofacial morphogenesis (Billington et al 2015; Green et al 2015; Hu et al 2015a; Hu et al 2015c; Smith et al 2015; Young et al 2014). These studies have shown that morphometric analyses can significantly add to mechanistic studies of development and thus that morphometrics and 3D imaging of embryos have significant potential for developmental biology.…”
Section: Future Directions - Integrating Molecular and Anatomical Imamentioning
confidence: 99%